Die-punch zlomenina fossa scaphoidea distálního radia - Šebesta, Petr; Tlustý, Zdeněk (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2021)
Even though the die-punch fragment of the distal radius fracture was described as early as in 1962, its detection may be crucial to select the optimal therapy even nowadays. Typically, the die-punch fragment is located in the lunate fossa. It can, however, also be located in the radial column. The patient with the die-punch fracture of the scaphoid fossa, treated by us with open reduction and plate osteosynthesis from two surgical approaches, is presented in our case report. Key words: die-punch fracture, distal radius, surgical treatment.
Keywords: radius; kosti zápěstní; kostní destičky; fraktury vřetenní kosti; Radius Fractures; Wrist Joint; vnitřní fixace fraktury; lidé; zápěstní kloub; Bone Plates; Fracture Fixation, Internal; Radius; Carpal Bones; Humans